2015
DOI: 10.1530/eje-15-0080
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Medical consequences of doping with anabolic androgenic steroids: effects on reproductive functions

Abstract: Anabolic androgenic steroids (AASs) are appearance and performance-enhancing drugs (APEDs) used in competitive athletics, in recreational sports, and by body-builders. The global lifetime prevalence of AASs abuse is 6.4% for males and 1.6% for women. Many AASs, often obtained from the internet and dubious sources, have not undergone proper testing and are consumed at extremely high doses and in irrational combinations, also along with other drugs. Controlled clinical trials investigating undesired side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
124
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 96 publications
(89 reference statements)
0
124
0
16
Order By: Relevance
“…Such disorders concern stunted growth, among adolescents, where bone maturation becomes fast and then stops at an early age 45 , liver tumors, several conditions regarding sex characteristics, disorders of the reproductive system, and finally, abnormal enlargement of the heart muscles and blood lipid abnormalities which lead to cardiovascular ailments 46 . The overuse of steroids is revealed overwhelmingly by volatility, acne, rapid muscle augmentation and, additionally, male-type hair growth, deepening of the voice and enlargement of the clitoris in teen girls and young women 47 . It is strongly recommended that children fully understand the concept of using anabolic steroids which involves health risk, the possibility of legal trouble and the feeling of fraud and responsibility on the whole.…”
Section: Anabolic Steroids and Childhoodmentioning
confidence: 99%
“…Such disorders concern stunted growth, among adolescents, where bone maturation becomes fast and then stops at an early age 45 , liver tumors, several conditions regarding sex characteristics, disorders of the reproductive system, and finally, abnormal enlargement of the heart muscles and blood lipid abnormalities which lead to cardiovascular ailments 46 . The overuse of steroids is revealed overwhelmingly by volatility, acne, rapid muscle augmentation and, additionally, male-type hair growth, deepening of the voice and enlargement of the clitoris in teen girls and young women 47 . It is strongly recommended that children fully understand the concept of using anabolic steroids which involves health risk, the possibility of legal trouble and the feeling of fraud and responsibility on the whole.…”
Section: Anabolic Steroids and Childhoodmentioning
confidence: 99%
“…AAS abuse, because of their anabolic effects, is detrimental to health [2][3][4][5]; nonetheless, AASs are widely used by athletes to increase muscle mass and power or enhance physical endurance [6]. Human and animal studies have reported discordant results regarding the cardiac and metabolic complications of AAS abuse [5,[7][8][9][10][11], with some suggesting that testosterone improves myocardial lipid metabolism [12] and may act as a cardioprotectant and coronary vasodilator comparable to conventional antiischemic drugs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, ANA, LET and EXE are included in the Word Anti-Doping Agency Prohibited List [7]; these drugs are used in combination with anabolic steroids to prevent the onset of gynecomastia by estrogenic excess; aromatase inhibitors are also used by doped athletes as post cycle therapy in order to promote restoration of hypothalamic-pituitary-testicular axis integrity [8,9].…”
Section: Introductionmentioning
confidence: 99%